Segmentation of Identical and Simultaneously Played Traditional Music Instruments using Adaptive - Yoyon K. Suprapto; Mauridhi H. Purnomo; Mochamad Hariyadi (IPTEK The Journal for Technology and Science, 2009)
Nowadays, mining of the musical ensemble has become very crucial since the information inside a musical ensemble is required by any musical contents services. In this research, we introduce Gamelan as one of the Indonesian traditional music instruments as our research objective. To indicate the changes of Gamelan features (i.e. tempo also the hammer struck styles) the segmentation of Gamelan music instruments is required as the music tagging tools. Adaptive LMS is employed for segmenting identical instruments that are played in the concurrent fashion. The target is to find how many instruments are played at the same time or separated by very short time (≤ 1 ms). The experiment results demonstrate robust detection with 0.02 ms accuracy for segmenting identical and simultaneously played Gamelan instruments. These results are employed for indicating the changes of Gamelan features, such as tempo also the hammer struck styles.